Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/cancers15020333
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Complications of Radiotherapy in Uveal Melanoma

Abstract: Uveal melanoma is the most common primary malignant intraocular tumor in adults. Radiation therapy has replaced enucleation and is now the preferred treatment in most cases. Nonetheless, around 70% of patients develop radiation-related complications, some of which are vision-threatening. The objective of this review is to present the most important complications associated with radiotherapy in the treatment of uveal melanoma and their pathogenesis, incidence, risk factors, and available preventive and therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 78 publications
0
23
0
1
Order By: Relevance
“…Indeed, conservative treatment that is performed in approximately 70% of cases consists of RT that can be delivered in the presence of small-sized tumors by implantation of intraocular radioactive plaques (ruthenium or iodine) or in the presence of medium-sized tumors by external beam-accelerated protons ( 17 ). The key point in performing conservative treatment is represented by the preservation of the optic nerve, whose damage is related to the reduction or loss of vision ( 18 ). Thus, the spatial relationship between tumor and optic nerve is crucial and the choice of external beam protons therapy is based on the achievement of a very steep “fall-off” of RT dose outside the clinical target volume ( 19 ).…”
Section: Low Electron Energy Flash Therapymentioning
confidence: 99%
“…Indeed, conservative treatment that is performed in approximately 70% of cases consists of RT that can be delivered in the presence of small-sized tumors by implantation of intraocular radioactive plaques (ruthenium or iodine) or in the presence of medium-sized tumors by external beam-accelerated protons ( 17 ). The key point in performing conservative treatment is represented by the preservation of the optic nerve, whose damage is related to the reduction or loss of vision ( 18 ). Thus, the spatial relationship between tumor and optic nerve is crucial and the choice of external beam protons therapy is based on the achievement of a very steep “fall-off” of RT dose outside the clinical target volume ( 19 ).…”
Section: Low Electron Energy Flash Therapymentioning
confidence: 99%
“…Die Strahlenretinopathie ist eine Gefäßveränderung, die durch die Einwirkung von Protonen, β- oder γ-Strahlung auf die Gefäßwandarchitektur ausgelöst wird 24 , 25 . Strahlenretinopathien können nach perkutaner Radiatio mit Röntgenstrahlen, nach Brachytherapie mit 106 Ruthenium-Applikatoren bzw.…”
Section: Strahlenretinopathieunclassified
“…The increase in the popularity of brachytherapy was largely influenced by the publication of the results of the Collaborative Ocular Melanoma Study (COMS), which showed the lack of an advantage of enucleation over brachytherapy in terms of distant metastases and survival in the case of small- and medium-sized tumors [ 3 , 19 ]. In a COMS study, tumor size was defined as follows: small: 1.5–2.4 mm in height and 5–16 mm in diameter; medium: 2.5–10 mm in apical height and ≤16 mm in diameter; and large: >10 mm in apical height and >16 mm in diameter; these terms will be used to describe tumors of these dimensions in the remainder of this article, unless otherwise noted [ 3 , 11 ]. Brachytherapy has gradually become the most commonly used treatment for choroidal melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of these methods include their minimal invasiveness, excellent local tumor control, relatively wide availability and low costs [ 20 , 25 , 26 , 28 , 29 ]. Some researchers have indicated their disadvantages in the form of lower precision and the associated higher number of post-radiation complications, mainly secondary glaucoma and enucleation compared with brachytherapy and proton therapy [ 11 , 20 , 30 ]. Other studies report no significant differences in the rate of complications between these therapies [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation